PENGUJIAN POTENSI BAKTERI ENDOFIT TERHADAP PERTUMBUHAN POPULASI NEMATODA SISTA KUNING (Globodera rostochiensis) PADA TANAMAN KENTANG (Solanum tuberosum L.) - Ulfah Utami; Lilik Hariani; Retno Setyaningrum (SAINSTIS, 2012)
Yellow Nematoda sista (Globodera rostochiensis) is one of interfering plant organism in potatoes plants that bothers farmers in Indonesia. Many controls done by farmers during this time uses chemist pesticide. The using of chemist pesticide  continuously  can  threaten  human  environment  and  healthy.  The existence of endofit bacteria might became one of nematode controlling agent which is hospitable, because endofit bacteria can produce toxic compound in nematode. The aim of this research is to find out the filtrate potential of endofit bacteria to the growth of yellow nematode sista population (Globodera rostochiensis) in potatoes plants.  This research is done in Microbiological and Greenhouse Laboratory, Biology Department, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang and Pest and Plant Disease Laboratory, Agriculture Faculty, Universitas Brawijaya Malang.  This research is done in December  2011  until  April  2011  by  using  Rancangan  Acak  Lengkap  (RAL) method. Bacterial filtrate is made in a way of making endofit bacteria grow in TSB  media  for  48  hours,  then  disentrifugasi  with  speed  13.000  rpm  for  15 minutes. Next, it is tested in yellow nematode sista in potatoes plants in the greenhouse. The result of this research shows that endofit bacteria filtrate can obstruct the growth of sista Globodera rostochiensis population. Three from those six isolates which have high ability in pressing sista Globodera rostochiensis population in 100 gram of soil are isolate AA (91%), DH (81%) and BE (81%). Isolate AA can press sista Globodera rostochiensis population in the high scale, which reach until 91%. All endofit bacteria isolate (Isolat AA, AH, BA, BE, DA and DH) can increase the growth of potatoes plants, they are the height of plant and the weight of potatoes plants root.